Reconstructing poverty-related shame among urban seniors in china: an exploration of their narrated experiences and a reflection on anti-poverty interventions - Chen, Y-Y; Hong, L; Walker, RL (Springer, 2020)
Poverty is an objective state, as well as a set of subjective experiences. This study explored how low-income seniors in urban China make meaning under the pressures of poverty-related shame. Based on two rounds of in-depth interviews with participants in Beijing, spanning 9 years, the researchers concluded that low-income seniors feel deprivation, experiences of being belittled and inferior and a sense of self-deprecation due to material scarcity. Under such pressures, the seniors actively reconstruct poverty-related experiences, demonstrating that older people living in poverty have a powerful meaning-making system, which serves as evidence of their resilience. However, reconstructing experiences of poverty should not be taken for granted, but be regarded as an appeal for dignity-oriented social policies. This rich meaning-making system could be a foundation upon which anti-poverty advocates adopt and advance various strengths-based interventions. These findings also point to implications for quality of life research with older people living in poverty and anti-poverty measures for this population in other developing contexts.